Low dose anti-inflammatory radiotherapy for the treatment of pneumonia by covid-19: A proposal for a multi-centric prospective trial. (September 2020) - Algara, M.; Arenas, M.; Marin, J.; Vallverdu, I.; Fernandez-Letón, P.; Villar, J.; Fabrer, G.; Rubio, C.; Montero, A.
Highlights: Interstitial bilateral pneumonia is the main complication of severe COVID-19. Low-dose radiation therapy (LD-RT) has well-known anti-inflammatory effects. LD-RT can interfere with the hyper-inflammatory cascade associated with severe COVID-19. LD-RT could reduce the severity of associated cytokine release caused by COVID-19. This trial will evaluate efficacy of lung LD-RT for interstitial COVID-19 pneumonia. Abstract: Background: COVID-19 is a highly contagious viral infection with high morbidity that is draining health resources. The biggest complication is pneumonia, which has a serious inflammatory component, with no standardized treatment. Low-dose radiation therapy (LD-RT) is non-invasive and has anti-inflammatory effects that can interfere with the inflammatory cascade, thus reducing the severity of associated cytokine release and might be useful in the treatment of respiratory complications caused by COVID-19. Study design and methods: This multicentric prospective clinical trial seeks to evaluate the efficacy of bilateral lung LD-RT therapy as a treatment for interstitial pneumonia in patients with COVID-19 for improving respiratory function. This prospective study will have 2 phases: I) an exploratory phase enrolling 10 patients, which will assess the feasibility and efficacy of low-dose lung irradiation, evaluated according to an increase in the PaO2/FiO2 ratio of at least 20% at 48–72 h with respect to the pre-irradiation value. If a minimum efficiency of 30% of the patients is not achieved, the study will not be continued. II) Non-randomized comparative phase in two groups: a control group, which will only receive pharmacological treatment, and an experimental arm with pharmacological treatment and LD-RT. It will include 96 patients, the allocation will be 1: 2, that is, 32 in the control arm and 64 in the experimental arm. The primary end-point will be the efficacy of LD-RT in patients with COVID-19 pneumonia according to an improvement in PaO2/FiO2. Secondary objectives will include the safety of bilateral lung LD-RT, an improvement in the radiology image, overall mortality rates at 15 and 30 days after irradiation and characterizing anti-inflammatory mechanisms of LD-RT by measuring the level of expression of adhesion molecules, anti-inflammatory cytokines and oxidative stress mediators. Trial registration: ClinicalTrial.gov NCT-04380818 https://clinicaltrials.gov/ct2/show/NCT04380818?term=RADIOTHERAPY&cond=COVID&draw=2&rank=4 .